Norm-Value Relationship in Islamic and Western Law / İslam ve Batı Hukuk Düşüncesinde Norm-Değer İlişkisi - Kurban, Yasin (Journal of History Culture and Art Research, 2018)
Abstract The law regulating interpersonal relations arises from society. In general terms, the law, which is the system of norms, uses both material and moral sanctions to force the individual to obey the norm. While the penalties and the administrative sanctions constitute the material sanctions, the world of values constitutes the spiritual dimension of obedience to the norm. Basically, it is not just punishments that lead the individual to obey to the norm but it is the response that what the order or prohibition of the norm finds in the world of values that exist in the inner world of the individual. In the philosophy of law, this situation is called the norm-value relationship. This study examines the norm-value relationship in the context of the "human model" created by the western civilization after industrial revolution and enlightenment, and the meaning given to the human in Islamic civilization. The study also examines the two civilizations in the context of norms based on value patterns. Öz İnsanlar arası ilişkileri düzenleyen hukuk toplumdan doğar. Genel bir ifadeyle normlar sistemi olan hukuk, bireyi norma itaate zorlarken hem maddi hem de manevi müeyyideler kullanır. Hukukun maddi müeyyidesini cezalar ve idari yaptırımlar oluştururken, norma itaatin manevi boyutunu değerler dünyası oluşturur. Temelde bireyi norma itaate götüren şey sadece cezalar değil, normun emrettiği ya da yasakladığı şeyin bireyin iç dünyasında var olan değerler dünyasında bulduğu karşılıktır. Hukuk felsefesinde bu duruma norm-değer ilişkisi denmektedir. Bu çalışmada özellikle sanayi devrimi ve aydınlanma sonrası Batı medeniyetinin “yarattığı” insan modeli ve İslam medeniyetinin insana yüklediği anlam çerçevesinde norm-değer ilişkisi ele alınmış ve normların dayandığı değerler dünyası mukayeseli olarak incelenmeye çalışılmıştır.